Sustainable economic development : perspectives from political economy and economics pluralism - Meramveliotakis, Giorgos; Manioudis, Manolis (Abingdon : Routledge, 2025)
Drawing on political economy and economic pluralism, this book explores issues in sustainable economic development from a macro perspective. In contrast to the vast majority of studies on contemporary development problems, which are focused on micro-level theory, method, and policy, this volume brings together both heterodox and mainstream perspectives. The international cast of contributors thus brings a pluralistic approach to core contemporary topics including digital transformation, climate change, degrowth and the effects of the pandemic crisis. Methods range from frameworks used to analyse public policy and institutional change, to modes of analyses including historically grounded narratives and conceptualisations of grand theories. Each chapter surveys the origins, development, key features, applications, and frontiers of a particular viewpoint, framework, or mode of analysis. This book makes a vital contribution to the literature on economic development, sustainable development, capitalism, and sustainability more broadly.
Introduction - Sustainable Economic Development: Setting the SceneGiorgos Meramveliotakis & Manolis Manioudis PART I: THE POLITICAL ECONOMY OF SUSTAINABLE DEVELOPMENT 1. The Vagaries and Volatilities of Mainstream Development Evonomics: A Personal AccountBen Fine 2. Reconsidering the role of economists and economics: Towards an 'institutional' ecological economicsPeter Söderbaum PART II: HISTORY OF ECONOMIC THOUGHT AND SUSTAINABLE DEVELOPMENT 3. On the limits of growth in Classical Political EconomyMichel S. Zouboulakis 4. Economic growth and social sustainability. How useful can it be to go back to the research programme of the German historical school?Vitantonio Gioia 5. Stages of capitalist development and maximum marine plastic pollution and the SDGsPeter J. Jacques PART III: DEGROWTH, URBAN ECONOMICS AND SUSTAINABLE DEVELOPMENT 6. A Review of the Political Critique to the Idea of Sustainable DevelopmentSotirios K. Bellos 7. Just Ecological Political Economy: A Radical Anti-Thesis of Environmental and Ecological EconomicsFranklin Obeng Odoom PART IV: GLOBALIZATION, CLIMATE CHANGE AND CRISES 8. Alternative Globalization Dynamics for a more Sustainable Development and Growth ProcessKyriaki I. Kafka9. Climate Change and Sustainable Development: A Global South PerspectiveYing Chen PART V: DIGITAL TRANSFORMATION, INNOVATION AND THE KNOWLEDGE ECONOMY 10. Towards Industry 6.0 and Techno-centric vs Human-centric Smart Balancing: The Journey from Industry 4.0 towards Industry and Society 5.0 and BeyondElias G. Carayannis, Pantelis C. Kostis, Kyriaki I. Kafka & Theodora Valvi11. The long and co-evolutionary path to green transition: history, technology, innovation and new policy paradigmsAntonios Angelakis & Manolis Manioudis PART VI: INFRASTRUCTURE, CULTURE AND GENDER 12. Infrastructure Capital and Growth: What can we learn from region-level data?Charalambos Arachovas 13. Cultural Background as a Crucial Factor for Sustainable DevelopmentPantelis C. Kostis14. Reducing the Gender Digital Divide: Inequalities, Feminism and TechnologyNick Drydakis
Keywords: BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economics / General; Sustainable development